Carbon dioxide treatment modulates phosphatidic acid signaling and stress response to improve chilling tolerance and postharvest quality in paprika - Park, Me-Hea; Ku, Kang-Mo; Do, Kyung-Ran; Eum, Hyang Lan; Cho, Jae Han; Park, Pue Hee; Malka, Siva Kumar (Frontiers in Plant Science, 2023)
Introduction Paprika (Capsicum annuum L.) is prone to chilling injury (CI) during low-temperature storage. Although recent findings suggest that CO2 treatment may protect against CI, the effects of short-term CO2 treatment on CI and the underlying molecular mechanisms in paprika remain unknown. Therefore, this study aimed to examine the effect of short-term CO2 treatment on CI and postharvest quality in paprika during storage at cold storage and retail condition at physio-biochemical-molecular level. Methods Paprika was treated with 20 and 30% CO2 for 3 h and stored at 4°C for 14 days, followed by additional storage for 2 days at 20°C (retail condition). Fruit quality parameters, including weight loss, firmness, color, and pitting were assessed, and the molecular mechanism of the treatment was elucidated using transcriptomic and metabolomic analyses. Results Short-term treatment with 20 and 30% CO2 effectively maintained paprika quality during cold storage and retailer conditions, with reduced surface pitting, a common symptom of CI. Additionally, transcriptomic and metabolomic analyses revealed that 20% CO2 treatment induced genes associated with biosynthesis of phosphatidic acid (PA), diacylglycerol, triacylglycerol, and stress response, metabolites associated with phasphatidyl inositol signaling, inositol phosphate metabolism, and starch and sucrose metabolism. Conclusion CO2 treatment activates PA biosynthesis through PLD and PLC-DGK pathways, and induces inositol phosphate, starch, and sucrose metabolism, thereby regulating chilling stress response via the ICE-CBF pathway. These findings suggest that short-term CO2 treatment enhances resistance to cold-induced injury and preserves postharvest quality in non-climacteric fruits, such as paprika, through activation of PA signaling, which improves membrane stability during cold storage and distribution.